Regional differences in crop production at the level of Slovakia’s districts between 2004 and 2022 - Némethová, Jana; Vilinová, Katarína; Rybanský, Ľubomír (Quaestiones Geographicae, 2025)
The aim of this study was to analyse the similarity between the districts of Slovakia with regard to the structure of the cropping area of eight crops in each of the three periods 2004–2009, 2010–2015 and 2016–2022, and to compare the results between these periods. We used cluster analysis, specifically the k-means method, to analyse similarity. For each district, the average cultivation area of each crop was determined for the periods of years under study. For the similarity of the cropping area structure, we used the percentage share of each crop in the cropping area of the district. The results of the study indicate regional differences in crop production in Slovakia and the identification of two clusters in each period under study. Comparing the profiles of clusters 1 and 2 for the periods we can see a considerable similarity, which indicates the stability of crop cultivation in Slovakia over the last 20 years. In cluster 1, cereals, grain maize and oilseeds gained higher shares of the district’s cropping area. Districts with the most favourable natural conditions for crop production and with higher crop diversification were included in this cluster. Cluster 2 included districts with higher shares of cropping areas of multi-annual fodder crops, potatoes and leguminous crops. The districts are characterised by less favourable soil-climatic conditions for crop cultivation.